Total Physical Response Method dalam menguasai mufradat pada Siswa MI Ihyaul Ulum Gresik - Nurul Islamiyah; Ahmad Faisal Zam Ani; Umi Hanifah (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2025)
The purpose of this study is to examine the Total Physical Response (TPR) method in mastering vocabulary among students at MI Ihyaul Ulum Gresik. This research employs a quantitative approach with a quasi-experimental design using a control group pre-test and post-test approach. The study Subject consists of 20 students from Class A as the experimental group and 36 students from Class B as the control group. The data collection techniques used in this study include observation, interviews, documentation, and questionnaires. Meanwhile, the data analysis techniques employed consist of descriptive and inferential analysis. The research results indicate that before the treatment (pretest), the average vocabulary mastery score of students in the experimental class was 67.65, while in the control class, it was recorded at 67.05. After applying the Total Physical Response method, the average score in the experimental class increased to 85.35. Inferential analysis revealed a significant difference between the pretest and posttest results, with a significance value (p-value) of 0.000 < 0.05. This study proves that the Total Physical Response method is effective in improving vocabulary mastery among fifth-grade students at MI Ihyaul Ulum Gresik.